2019
DOI: 10.1007/s40333-019-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Eco-physiological studies on desert plants: germination of Halothamnus iraqensis Botsch. seeds under different conditions

Abstract: With the aim to investigate if the halophyte Halothamnus iraqensis Botsch. can be suitable for re-vegetation and remediation of salt-affected lands, this study evaluated (1) the effects of photoperiod, thermoperiod, storage period and wings' presence on its seed germination, and (2) the ability of its seeds to have successful germination recovery after salt stress. Germination tests in different photoperiods (12 h light/12 h darkness and total darkness) and thermoperiods (15°C/20°C and 20°C/25°C) were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Overall, freshly collected seeds of all the selected species showed high germination percentages and showed similar germination patterns. Higher germination response of freshly collected seeds have been reported previously for these species, believed to be an adaptation strategy that coincides with the rainfall patterns in the Arabian desert (Bhatt et al, 2019a,b,c). In the Arabian desert, most halophytes mature during November–December when temperature is low, and the chances of rainfall are high.…”
Section: Discussionsupporting
confidence: 67%
“…Overall, freshly collected seeds of all the selected species showed high germination percentages and showed similar germination patterns. Higher germination response of freshly collected seeds have been reported previously for these species, believed to be an adaptation strategy that coincides with the rainfall patterns in the Arabian desert (Bhatt et al, 2019a,b,c). In the Arabian desert, most halophytes mature during November–December when temperature is low, and the chances of rainfall are high.…”
Section: Discussionsupporting
confidence: 67%
“…Wind-dispersal allows seeds to increase their chances of finding a suitable location for germination. Several studies on wind-dispersed seeds have indicated that the wings play an important role in controlling seed dormancy and germination requirements, such as light, temperatures and salinity (e.g., El-Keblawy, 2014, Bhatt and Santo, 2018, Bhatt et al., 2019). In our study, seeds of three species ( S .…”
Section: Discussionmentioning
confidence: 99%
“…Salinity tolerance strategies not only vary among species, but also among the different stages of plant growth [7,23]. In general, salinity either hinders the germination of salt-sensitive species (i.e., glycophyte) or delays the germination of salt-tolerant species (i.e., halophyte species) [24][25][26][27][28][29]. Similarly, the seedling stage is also reported to be highly sensitive to salinity stress [30,31].…”
Section: Introductionmentioning
confidence: 99%